United Nations Environment Assembly attendees underestimate public willingness to contribute to climate action - Ximeng Fang; Joshua Ettinger; Stefania Innocenti (Communications Earth & Environment)
Abstract Researchers are increasingly examining policy officials’ perceptions of public opinion on climate change. However, limited research has examined the perceptions of individuals who participate in international-level environmental policy meetings. Here we show that 2024 United Nations Environment Assembly attendees (N = 191) underestimate global public willingness to contribute 1% of their personal income to climate action by nearly half on average (37% versus 69% in actuality). This finding suggests that those who are directly and indirectly involved in setting global environmental policies may have a stronger public mandate for ambitious climate action than they realize. We discuss the implications of this finding and highlight the need for further research on international policy actors’ perceptions of public opinion; the factors that shape these perceptions; and how these perceptions may influence policy outcomes.